Determinants of unfavourable treatment outcomes of drug-resistant tuberculosis cases in Malaysia: a case–control study - Mohd Fahmin Kamarul Zaman; Nik Rosmawati Nik Husain; Mohd Yusof Sidek; Zamzurina Abu Bakar (BMJ Open)
Objectives The emergence of drug-resistant tuberculosis (DR-TB) complicates TB management and poses significant challenges to achieve favourable treatment outcomes. Treating DR-TB is more complex and costly, requiring extended treatment durations and consideration of drug toxicity and side effects. This study aims to identify the determinants of unfavourable treatment outcomes among DR-TB patients in Malaysia.Design Retrospective case–control study.Setting Secondary data from the National Tuberculosis Registry (NTBR) across two states in Malaysia.Participants All reported DR-TB cases in the NTBR between 2016 and 2020 from Selangor and Wilayah Persekutuan Kuala Lumpur, Malaysia. Cases still undergoing treatment at the time of analysis were excluded. A total of 403 cases were analysed, with 181 (44.9%) experiencing unfavourable treatment outcomes and 222 (55.1%) having favourable treatment outcomes. The case group consists of individuals with DR-TB who experienced unfavourable treatment outcomes, while the control group comprises individuals with DR-TB who achieved favourable treatment outcomes.Outcome measures Unfavourable treatment outcomes, defined as death, treatment failure or loss to follow-up, were assessed. Predictors of these outcomes were identified through multiple logistic regression analysis.Results Significant determinants of unfavourable treatment outcomes included being male (adjusted OR (aOR) 2.38, 95% CI 1.44 to 3.94), being single or divorced (aOR 1.61, 95% CI 1.03 to 2.49), having no formal education (aOR 3.09, 95% CI 1.49 to 6.41), people living with HIV (aOR 2.87, 95% CI 1.40 to 5.87) and having DR-TB categorised as rifampicin-resistant tuberculosis (aOR 3.34, 95% CI 1.90 to 5.86) or multidrug-resistant/pre-extensively drug-resistant/extensively drug-resistant-TB (aOR 2.57, 95% CI 1.52 to 4.33).Conclusion The findings reveal a high proportion of DR-TB cases with unfavourable treatment outcomes and identify their key determinants. Targeted interventions addressing these factors are essential to improve treatment outcomes.